How do warnings influence cyclists' reaction to conflicts? Comparing acoustic and vibro-tactile warnings in different conflicts on a test track. (October 2022) - Strohaeker, Elke Henriette; Moia, Alessandro; Steinmann, Jochen; Hagemeister, Carmen
Highlights: The influence of cyclist warnings to conflicts with other road users was evaluated. Cyclist warnings effectively shortened reaction time. Acoustic warnings were more effective than vibro-tactile warnings. The participants did not have a significant warning type preference. Different learning effects related to the adoption of the warnings were observed. Abstract: An on-bike warning system has great potential to increase safety of cyclists. For an effective warning system, the implementation of warning signals is fundamental. However, more knowledge about the cyclist specific design of warnings and the influence of warnings on the cyclist is needed. To analyze the benefit of warnings in conflicts and the reaction pattern of cyclists we conducted a test-track experiment. We evaluated the data of 62 participants who were divided into three warning groups (between-subjects) and encountered different situations (within-subjects). The warning groups either received acoustic, vibro-tactile or no warnings. The situation variable consisted of three conflicts and two false warnings in the groups with warnings. We measured significantly shorter reaction times of persons who received acoustic and vibro-tactile warnings compared to the persons without warning. Furthermore, acoustic warnings led to shorter reaction times compared to vibro-tactile warnings. The reaction pattern was described by different bicycle dynamics variables. It was mostly influenced by the situation and rarely by the warning group. Based on the velocity curves and reaction times we identified learning effects describing how the warned participants adopted the warning system over the five situations. These findings indicate that a warning system offers great safety benefits to cyclists. Based on the current results, acoustic warnings are recommended when an urgent reaction is required.